Exercício Resolvido de Derivadas de Funções
b)
\( \displaystyle y=\frac{1}{x} \)
\[ \bbox[#99CCFF,10px]
{f´(x)=\lim_{\Delta x\rightarrow 0}{\frac{f(x+\Delta x)-f(x)}{\Delta x}}}
\]
Temos
\( f(x+\Delta x)=\frac{1}{x+\Delta x} \)
e
\( f(x)=\frac{1}{x} \)
\[
\begin{align}
y´ &=\lim_{\Delta x\rightarrow 0}{\frac{1}{\Delta x}}\left[\frac{1}{x+\Delta x}-\frac{1}{x}\right]=\lim_{\Delta x\rightarrow 0}{\frac{1}{\Delta x}}\left[\frac{x-(x+\Delta x)}{x(x+\Delta x)}\right]=\\[5pt]
&=\lim_{\Delta x\rightarrow 0}{\frac{1}{\Delta x}}\left[\frac{x-x-\Delta x}{x(x+\Delta x)}\right]=\lim_{\Delta x\rightarrow 0}{\frac{1}{\cancel{\Delta x}}}\left[\frac{-\cancel{\Delta x}}{x(x+\Delta x)}\right]=\\[5pt]
&=\lim_{\Delta x\rightarrow 0}{\frac{-1}{x(x+0)}}\ \phantom{{}}\text{=}-\frac{1}{x^{2}}
\end{align}
\]
\[ \bbox[#FFCCCC,10px]
{y´=-{\frac{1}{x^{2}}}}
\]